2007
DOI: 10.1139/t07-016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of desiccation of a mining waste

Abstract: The paper presents an analysis of the desiccation process in mining materials, based on physical laws. Due to the process complexity, most of the previous approaches used have an empirical basis. In this case, however, a formulation using coupled hydromechanical equations has been considered. To show the capabilities of the theoretical framework, several laboratory tests were performed, and afterwards a numerical simulation of the measured variables was attempted. The material tested was a metallurgical waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 26 publications
10
77
1
Order By: Relevance
“…Tang et al (2008), Tang et al (2010a) and Costa et al (2013) were able to show that there was an influence of the desiccation rate in the amount of cracks produced. Rodríguez et al (2007) observed that the effects of soil thickness on the cracking water content were not noticeable for very thin soil layers. Peron et al (2009) looked at free and constrained desiccation, and crack patterns.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…Tang et al (2008), Tang et al (2010a) and Costa et al (2013) were able to show that there was an influence of the desiccation rate in the amount of cracks produced. Rodríguez et al (2007) observed that the effects of soil thickness on the cracking water content were not noticeable for very thin soil layers. Peron et al (2009) looked at free and constrained desiccation, and crack patterns.…”
Section: Accepted M Manuscriptmentioning
confidence: 94%
“…Abu-Hejleh and Znidarčić (1995) described the cracking process in terms of the consolidation and shrinkage of the desiccating material. Rodríguez et al (2007) presented a general approach, introducing coupled hydro-mechanical behavior of the soil in unsaturated conditions to simulate the cracking in their laboratory experiments on mine tailings. Shin and Santamarina (2011) utilized an effective stress approach and explained the crack initiation process using the evolution of the air-water interface membrane as the soil dries.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The results show that the tensile strength-suction evolution depends strongly on both drying and compaction paths. These results are compared with recent published results by [2]. In parallel, the clayey soil is studied by a mercury porosimetry test to characterize the pore distribution network.…”
Section: Introductionmentioning
confidence: 90%
“…Most recent works dealing with cracking in drying soils consider the tensile strength as failure criterion to define whether a crack initiates or not in a particular point of the soil mass ( [10], [15], [16], [22]). This failure criterion, however, has been criticised as too simplistic ( [21]).…”
Section: Crack Initiationmentioning
confidence: 99%
“…While the soil is a continuous medium, the conventional coupled HM formulations used for porous media may apply. Therefore, soil drying up to the crack initiation can be simulated numerically by using standard finite element codes solving HM equations in unsaturated conditions [10].…”
Section: Crack Initiationmentioning
confidence: 99%